(untitled) (Palíndromo, 2019)
Some developments in the artistic field towards a greater horizontality are considered, which imply an emphasis on the process, experience or the role of the public as a participant in various degrees. An extended concept of the museum idea is suggested in this same line, and some examples of collaborative artistic practices are reviewed in which it is present in different forms and which refer to an artistic culture that prioritizes the experience, the process, the interaction, the action and personal and social development and transformation.